Educational Journeys Through Time: Overview and Impacts - Sanja Iguman Glušac; Predrag Krstić; Aleksandar Ostojić (Etnoantropološki Problemi)
This paper examines the profound impact of travel on educational experiences considering contemporary and historical journeys. It highlights the intricate relationship between education and experience, emphasizing their continued relevance in the context of globalization and technological change. Historically, travel has been a vital component of human existence, serving as a means to gain knowledge, broaden understanding, and foster intellectual and emotional resilience. From the Grand Tour of Europe to modern study abroad programs, travel has played a central role in many educational systems across different cultures. The main hypothesis suggests that travel was seen, beyond its logistical and recreational aspects, as a trigger of both personal and collective growth. The study employs historical analysis and a phenomenological approach to explore how landscapes, transitions, and cultural encounters influence educational outcomes. It underscores the importance of the passage—the often-overlooked segment of travel—as a dimension of transformation, meaning-making, and knowledge-gaining. Reflecting on the legacy of educational travel, from ancient philosophers and Renaissance humanists to modern-day programs, we question the evolving dynamics of mobility in a globalized world. Paper also discusses the shift from dangerous and arduous journeys to more pleasant and transformative experience.